The significance of financial distress on tax avoidance compared to gender diversity and social responsibility: a study from Indonesia / Ari Kamayanti ... [et al.] - -, Ari Kamayanti; -, Nur Qomariyah; -, Muhammad Muwidha; -, Widi Dwi Ernawati (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
The research aimed to examine the effect of Corporate Social Responsibility (CSR), Corporate Governance (CG), and financial distress on tax avoidance in manufacturing companies listed in Indonesia Stock Exchange during the period ranging from 2016 to 2020. By employing multiple regression analysis, it was found that CSR did not have an effect on tax avoidance. Contrastingly, CG proxied through the gender diversity of directors negatively affected tax avoidance. In contrast, board size and audit quality did not have an effect on tax avoidance. The study also supports previous findings that financial distress has a positive effect on tax avoidance. This study used rare variables combined which were CSR, CG and financial distress as independent variables to determine tax avoidance.